2017
DOI: 10.1039/c7ra04752e
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the existence of piezoelectric property of a bio-polymer – chitosan and its application in vibration sensors

Abstract: A variety of physical and chemical properties of bio-polymers like chitosan have been investigated although their inherent behavior, such as piezoelectricity, has not been investigated to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 17 publications
2
32
0
Order By: Relevance
“…Correspondingly, the piezoelectricity of chitin has been reported in the 1970s (Fukada & Sasaki, 1975), but literature concerning the piezoelectric sensitivity of chitosan is scarce. Piezoelectric sensitivity values of chitosan have been reported in our preliminary study (Hänninen, Rajala, Salpavaara, Kellomäki, & Tuukkanen, 2016) as well as in a recent study where the usage of chitosan in piezoelectric vibration sensors was reported (Praveen, Murugan, & Jayakumar, 2017).…”
Section: Introductionsupporting
confidence: 68%
“…Correspondingly, the piezoelectricity of chitin has been reported in the 1970s (Fukada & Sasaki, 1975), but literature concerning the piezoelectric sensitivity of chitosan is scarce. Piezoelectric sensitivity values of chitosan have been reported in our preliminary study (Hänninen, Rajala, Salpavaara, Kellomäki, & Tuukkanen, 2016) as well as in a recent study where the usage of chitosan in piezoelectric vibration sensors was reported (Praveen, Murugan, & Jayakumar, 2017).…”
Section: Introductionsupporting
confidence: 68%
“…[106] Copyright 2018, Springer Nature Publishers. [111] Copyright 2017, The Royal Society of Chemistry. Reproduced with permission.…”
Section: Polysaccharides Based Materialsmentioning
confidence: 99%
“…d-f) Reproduced with permission. Later, Jayakumar et al [111] studied the piezoelectric coefficient (d 33 ) by varying the temperature and pressure (Figure 3h). g) Dependence of piezoelectric strain constant d 14 = d′ 14 − id″ 14 with temperature for dried α-chitin measured at 10 Hz.…”
Section: Polysaccharides Based Materialsmentioning
confidence: 99%
“…Recently, there has been a growing interest in the biopiezoelectric materials to overcome these limitations. Polysaccharide materials [24][25][26][27], viruses [28][29][30][31], and self-assembled biomaterials [32,33] have been identified as good candidates, because their piezoelectric constants are higher than those of previous natural biomaterials, and they are possible to mass-produce. Especially, it has been found their physical and chemical properties can be modulated by their morphology, surface charges, and phases, and the piezoelectric response is directly related to these.…”
Section: Introductionmentioning
confidence: 99%
“…They combined the knowledge of pyroelectricity with their understanding of crystal structures and behavior, and demonstrated the first piezoelectric effect by using crystals of quartz and Rochelle salt. Since then, many researchers have discovered and reported the piezoelectric properties of organic [15,16], inorganic [7][8][9][10][11][12][13][14]17], and biomaterials [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introduction To Piezoelectric Effectmentioning
confidence: 99%